2020
DOI: 10.1158/1538-7445.am2020-6606
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 6606: Develop dual-targeted CAR-T cells to achieve RCC cures

Abstract: Clear cell renal cell carcinoma (ccRCC) is the major type of RCC and is among the 10 most common cancers in both men and women. ccRCC is characterized by the loss of chromosome 3p, where the von-Hippel-Lindau (VHL) gene is found. Its gene product, pVHL suppresses the hypoxia inducible factor (HIF) transcription factors and the deletion of VHL leads to HIF hyperactivation, upregulating the expression of many downstream genes involved in angiogenesis, metabolism, and cell-cycle regulation. Two gene products, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Our in vitro and in vivo preclinical studies using humanized mice bearing human RCC [ 132 ] have been encouraging from the standpoint of antitumor efficacy and minimal on-target off-tumor side effects [ 28 , 133 135 ]. Besides CAIX, oncofetal antigen 5T4 (with overexpression found in over 75% of RCC patient samples) [ 22 ] and the CD70 (overexpressed in about 40% of RCC patients) [ 86 , 88 , 136 ], are relevant targets to be further explored for the development of new cell immunotherapies for RCC management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our in vitro and in vivo preclinical studies using humanized mice bearing human RCC [ 132 ] have been encouraging from the standpoint of antitumor efficacy and minimal on-target off-tumor side effects [ 28 , 133 135 ]. Besides CAIX, oncofetal antigen 5T4 (with overexpression found in over 75% of RCC patient samples) [ 22 ] and the CD70 (overexpressed in about 40% of RCC patients) [ 86 , 88 , 136 ], are relevant targets to be further explored for the development of new cell immunotherapies for RCC management.…”
Section: Discussionmentioning
confidence: 99%
“…Another preclinical study evaluating allogeneic cells identified CD70 CAR-T binding epitopes that exhibited important antitumor activity against RCC cell lines and in a xenograft mouse model of RCC derived from patients [ 31 ]. Moreover, we developed dual-targeted anti-CAIX/CD70 CAR-T cells to enlarge the target cell population and mitigate tumor heterogeneity [ 87 , 88 ].…”
Section: Preclinical and Clinical Applications Of Adoptive Cell Thera...mentioning
confidence: 99%
“…In our study comparing G9 to G250, we observed superior in vivo antitumor efficacy as well as boosted in vivo expansion, better ex vivo migration and a wider therapeutic window of G9. To further enhance tumor killing efficacy and decrease the OTOT of CAIX targeted CAR-T cells, we have designed an anti-CAIX/CD70 dual-targeted CAR-T cell therapy that is activated in the presence of either CAIX or CD70, thus killing CAIX low expressing tumor cells and preventing potential antigen escape [59].…”
Section: Discussionmentioning
confidence: 99%